Metastatic lung adenocarcinoma favorable outcome with ITK-EGFR treatment in a smoker Metastatic lung adenocarcinoma favorable evolution with ITK-EGFR treatment in a smoker. - Exebio Jara, Joseph Jesús (2015)
Background: Lung cancer has highest mortality in both sexes. Current management of lung adenocarcinoma includes determining epidermal growth factor receptor (EGFR) mutational status as this is the target of erlotinib, a biologic therapy. Case report: A 62 yearold male with high smoking cancer risk presented chronic headache for a month, and magnetic resonance showed a brain tumor. Surgical specimen diagnosis was metastatic pulmonary adenocarcinoma by immunohistochemistry (TTF-1 (+)). An asymptomatic lesion in the right upper lobe of the lung was identified by tomography. Due to positivity to EGFR gene exon 21 mutation erlotinib was started; it was well tolerated by the patient. The patient died 31 months after diagnosis. Discussion: Treatment with erlotinib was initially indicated in the profile of an Asian and non-smoker woman patient. The overall survival rate with erlotinib in patients with non-small cell lung cancer is reported as 15.9 months, less time than with our patient, even considering his heavy smoker condition which should have decreased both the chance of having EGFR mutation and response to treatment.